SCOUT IDE Investigation: 1-Year Clinical Findings for a Conforming Porous Polymeric Lumbar Interbody Fusion Device. (1st September 2019) - Lu, Yi; Wu, Kyle; Krag, Martin H; Lavoie, Stephane; Bydon, Mohamad; Nunley, Pierce D; Chi, John H
Abstract: INTRODUCTION: This clinical investigation evaluates a novel conforming mesh device for single-level lumbar interbody fusion (IBF) treating degenerative disc disease. The device placed in the prepared disc space through a small portal and filled with bone graft in situ creates an endplate conforming large loadsharing footprint. Early/sustained improvements in pain and function are essential patient-centric metrics. These parameters combined with bone growth and safety must be demonstrated to warrant device use and future adoption. METHODS: This prospective multicenter investigation of 102 subjects yielded 99 subjects with 12-mo data. Mean age/BMI are 57/30.6, respectively, with balanced gender. Primary measures include Visual Analog Scale (VAS) for low back pain (LBP), Oswestry Disability Index (ODI) for low back function, fusion assessed by CT scan, and safety. RESULTS: Clinically relevant improvements are demonstrated in pain and function. At 12-mo postop, mean LBP VAS change from baseline is −50.3 mm (preop: 74.1, 12-mo: 23.6). This is improved over the 6-wk change from baseline of −45 mm. Similar trends are observed for lower extremity pain scores. Clinically relevant improvements in ODI also occur by 6-wk and continue to improve over time where the 6-wk mean ODI change from baseline is −16.9 compared 12-mo of −31.4 (pre-op: 53.6, 12 mo 21.8). Fusion rate of 96.9% (94/97). No investigation device-related serious adverse events occurred. High patient satisfaction rates reported early with 85.9% (85/99) rating satisfaction as Excellent/Good at 6-wk and maintained through 12-mo (89.7%, 87/97). CONCLUSION: Observed early clinical improvements by 6-wk postop are maintained and/or continue to improve over time. Combined with high fusion rates, demonstrated device safety to date, and compelling levels of patient satisfaction, these results are highly positive and support use of this device for IBF. Sustained results at 2-yr postop are both anticipated and forthcoming.